2022
DOI: 10.3389/fimmu.2022.820718
|View full text |Cite
|
Sign up to set email alerts
|

Tanreqing Injection Attenuates Macrophage Activation and the Inflammatory Response via the lncRNA-SNHG1/HMGB1 Axis in Lipopolysaccharide-Induced Acute Lung Injury

Abstract: The etiology of acute lung injury (ALI) is not clear, and the treatment of ALI presents a great challenge. This study aimed to investigate the pathogenesis and potential therapeutic targets of ALI and to define the target gene of Tanreqing (TRQ), which is a traditional Chinese medicine formula composed of five medicines, scutellaria baicalensis, bear bile powder, goat horn powder, honeysuckle and forsythia. Macrophage activation plays a critical role in many pathophysiological processes, such as inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It has been reported that SNHG1 participates in a variety of LPSinduced inflammation and promotes the production of proinflammatory cytokines [19,20]. Interestingly, SNHG1 is a direct transcriptional target of NFKB subunit p65 that promotes the expression of proinflammatory cytokines in acute lung injury (ALI) [21]. SNHG1 may form a positive feedback loop with the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SNHG1 participates in a variety of LPSinduced inflammation and promotes the production of proinflammatory cytokines [19,20]. Interestingly, SNHG1 is a direct transcriptional target of NFKB subunit p65 that promotes the expression of proinflammatory cytokines in acute lung injury (ALI) [21]. SNHG1 may form a positive feedback loop with the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the lncRNA SNHG1 mediated crosstalk with NFKB1 via two miRNAs, including miR-9-5p and miR-340-5p (Figure 6B). lncRNA SNHG1 has previously been reported to be significantly associated with inflammatory gene expression and promote LPS-induced inflammatory responses [19][20][21]. Thus, we speculated that SNHG1-miR-9-5p/miR-340-5p-NFKB1 axis might play an important role in the reduction in inflammation by cryotherapy by regulating NFKB1 expression.…”
Section: Lncrna-mirna-mrna Network Analysismentioning
confidence: 91%
“…Similarly, limiting RAGE-mediated inflammation may be beneficial in ARDS treatment. It is reported that Dexmedetomidine [ 234 ], Calycosin [ 235 ], and Tanreqing [ 236 ] alleviate inflammation mediated by RAGE and TLR4 receptors via inhibiting HMGB1 signaling. Notably, a clinical trial of Dexmedetomidine for ARDS in critical care COVID-19 patients is under investigation (NCT04358627).…”
Section: Emerging Pharmacologic Therapies For Ardsmentioning
confidence: 99%
“…In cholangiocarcinoma cell lines, SNHG1 is associated with increased proliferation and invasion, mediated by NF-κB activation through the miR-140/TLR4 axis, contributing to an inflammatory TME [ 171 ]. In an LPS-induced acute lung injury model, SNHG1 is upregulated in M1 polarized THP-1 cells, enhancing NF-κB activation and inflammation through interaction with HMGB1 [ 114 ]. However, SNHG1’s specific role in macrophage-related TME remains unexplored.…”
Section: Lncrnas That Modulate Macrophage Nf-κb Activity In Cancermentioning
confidence: 99%